Antibiotic susceptibility pattern and the indicator of decreased ciprofloxacin susceptibility of Salmonella enterica serovar Typhi isolated from Dhulikhel Hospital, Nepal. - Dhruba Acharya (2018)
Monitoring the antibiotic susceptibility pattern of Salmonella enterica serovar Typhi (S. Typhi) is important for efficiently managing cases of typhoid fever. In this study, the antimicrobial susceptibility patterns of 114 S. Typhi isolates, which were collected from a university hospital in Nepal during July 2009-December 2010, were investigated by disc diffusion assays. All of the S. Typhi isolates were sensitive to amoxycillin-clavulanic acid. More than 95% of the isolates were sensitive to chloramphenicol, ceftazidime, ceftriaxone, and cotrimoxazole. In addition, 1.7% of the studied isolates showed multiple drug resistance patterns. Of the 40 S. Typhi isolates, 32 strains (80%) showed nalidixic acid (NA) resistance with decreased susceptibility to ciprofloxacin (CIP). Importantly, we found the simultaneous presence of NA resistance and decreased susceptibility to CIP, suggesting that the resistance to NA is a reliable indicator of decreased CIP susceptibility (sensitivity, 97.5%; specificity, 100.0%). Furthermore, the sequencing of NA-resistant S. Typhi isolates showed a predominant amino acid alteration in the quinolone resistance-determining region (QRDR) of gyrA gene at position 83 from Ser→Phe. Two isolates with resistance to both CIP and NA had a double-mutation (Ser83→Phe and Asp87→Asn) in the QRDR of the gyrA gene, of which one had an additional amino acid mutation (Ser80→Ilu) in the QRDR of the parC gene.